Improving Special Education and Inclusion Course in Primary Mathematics Teacher Education Program - Canan SOLA OZGUC (Anı Publishing, 2021)
This study aimed to improve special education and inclusion courses given to pre-service teachers in a primary mathematics education program at a university in Turkey. The aim was to enhance their knowledge and skills and present solutions to problems occurring in courses given during the term and changes in the sense of efficacy of pre-service teachers. For this purpose, the research used qualitative and quantitative data collection methods based on the action research method. Shorter course duration and intense content were among the most important problems faced by the instructor. The course curriculum was adapted in line with the needs of primary school mathematics teachers. It was aimed to increase the effectiveness of teaching by providing a variety of materials. Pre-service teachers had the opportunity to gain experience working with special needs students by teaching them origami shapes in the special education and inclusion course. The data obtained from the scales at the end of the process revealed that teachers' sense of efficacy showed improvement regarding inclusion. Pre-service teachers were pleased to have such a course and offered suggestions to the course instructor. Based on the findings, the elements for improving this education are discussed, and suggestions are presented.